The Role Of Conservative Religious Movements in the Formation of Religious Moderation in Indonesia - Akmal, Maulidina; Khobir, Abdul; Anisa, Sofiatun; Azam, Nisrina Luthfiya (DAS Institute, 2025)
This article discusses the role of conservative religious movements in shaping religious moderation in Indonesia, particularly in the context of a pluralistic society undergoing constant social change. Amidst increasing globalization, digitalization, and the development of transnational religious thought, conservatism occupies a unique position because, on the one hand, it preserves the purity of religious teachings, but on the other hand, it can cause resistance to religious moderation programs. This study uses a literature review method to explore the concept of religious moderation, the nature of conservative movements, and their contribution to strengthening balanced religious practices. The results of the study show that conservative groups can play a positive role in religious moderation by safeguarding basic values and moral stability, as well as acting as a counterbalance between tradition and modernity. However, these groups also face challenges in the form of limited literacy on moderation, political influence, and a tendency to misunderstand moderation. This article offers several strategic solutions, such as strengthening religious dialogue, improving religious literacy, collaboration between conservative and moderate figures, reformulating the education curriculum, strengthening local cultural values, and state policy support. This study emphasizes that conservatism is not always an obstacle but can be an important partner in building constructive and sustainable religious moderation.